Efektivitas Social Customer Relationship Management di industri perhotelan: Dampaknya terhadap niat beli dan loyalitas pelanggan - Miyana Miyana; Endi Sarwoko; Teofilus Teofilus (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2025)
Social Customer Relationship Management (S-CRM) integrates traditional CRM with social media platforms, enabling more personalized and interactive communication between businesses and customers. In the hospitality industry, especially amid growing competition and digitalization, S-CRM plays a vital role in maintaining customer relationships and driving business outcomes. This study aims to analyze the effect of S-CRM on purchase intention and customer loyalty within 76 hotels under Azana Hospitality in Indonesia. Using a quantitative approach, data were collected from 395 respondents who had previously made reservations at Azana hotels, selected through convenience sampling. Structural Equation Modeling (SEM) with SmartPLS 4 was employed to test the measurement and structural models. The results show that S-CRM significantly influences both purchase intention and customer loyalty. Furthermore, purchase intention significantly mediates the relationship between S-CRM and customer loyalty. These findings highlight the theoretical implication that S-CRM enhances customer engagement and loyalty through increased intention to purchase. Practically, the study underscores the importance for hospitality businesses to invest in S-CRM strategies to build stronger customer relationships, improve brand loyalty, and ensure sustainable competitive advantage. This research contributes to the growing literature on digital CRM practices and offers valuable insights for hotel management and marketers.